Analysis of circular plate with tunable frequency - Syed Noh bin Syed Abu Bakar (Kulliyyah of Engineering, Internationai Islamic University Malaysia, 2015)
The study of plate with tunable frequency becomes an important study as it aids for more effective design of plate for the use of devices such as resonator (i.e. SJAs, speakers) or energy harvesting devices. This study explored on idea of a structure which its frequency may be tuned through the application of electrical means alone. This idea would eliminate the needs of extra mechanical structure in certain transportation such as aircraft. A circular plate is tuned through attaching a piezoceramic annular plate at the edge of a circular plate. By controlling the voltage applied to the piezoceramic annular plate, thus the radial load, the fundamental frequency of the circular plate may be tuned. The analysis is performed by using finite different method which coded through MATLAB®. The study is divided into two major parts. First part is the study of circular plate buckling problem in order to obtain the limit of radial load that may be applied by using attached piezoceramic annular plate. This will provide an information on significant radial load. Second part is the study of circular plate vibration problem which aim to look at the feasibility of using attached piezoceramic annular plate in tuning the circular plate frequency. For both, buckling and vibration problems, a parametric study was also performed. Results on vibration problem showed that the radial load applied through attached piezoceramic annular plate gave a significant range of frequency tuning for most configuration reported. Parametric study for buckling problem showed that the inner radius has a significant influence in critical buckling voltage except for the case of annular plate is thicker than the circular plate. Also, it is found that for inner radius far enough from the outer radius, the circular thickness only influence the critical buckling voltage when the circular plate has thickness near the annular plate or smaller. Lastly, the critical buckling voltage increases as the annular thickness increases regardless the annular plate is thicker or thinner than the circular plate. On the other hand, parametric study for vibration problem showed that the fundamental frequency is independent of the radius if the annular plate has equal thickness as the circular plate. While the similar may be conclude for the case where the annular is thicker than the circular plate but only for the if the inner radius is less than half of the outer radius. The fundamental frequency reduces rapidly as the inner radius became larger than half of the outer radius. For the case where the annular plate is thinner than the circular plate, the fundamental frequency increases with the change of the inner radius.